Faith and Fitness: Experiences, Challenges, and Coping Mechanism of Muslim Women Students in Participation in Physical Education Class at Notre Dame of Marbel University - Cardinas, Nerlyn Jane L.; Prio, Michelle V.; Salazar, Jene Reven P.; Pendon, John Paul S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study delved into the experiences, challenges, and coping mechanism of Muslim women students in their participation in physical education class at Notre Dame of Marbel University, City of Koronadal, Province of South Cotabato. Using qualitative descriptive research design, an in-depth interviews were conducted including transcriptions, identification of significant statements, creation and organization of concepts to themes which revealed various factors influencing their participation. Findings of the study highlights that Muslim women students often participate in physical education under academic compulsion with some benefits from teachers being considerate. Positive student-teacher relationship and social rapport from classmates helps to create more comfortable experiences for them. However, there were significant challenges that hinders their participation such as religious restrictions especially on dance movements, discomfort from high-intensity exercises, and burden of wearing a layered clothing during physical education classes. Also, the inadequate facilities, some teachers lack consideration and struggle maintaining religious practices. Some students shared an experiences of academic coercion which they feel pressured to participate despite personal discomfort. Students coping mechanism is to modify clothes to maintain modesty, minimizing interaction with the opposite sex, and avoids situation where they feel being judged. Additionally, to meet academic requirements they seek for reconciliation through prayer and bringing fans to help alleviate the discomfort. These findings highlight for more inclusive phyiscal education policies just like dress code accommodation, inclusive facilities, and culturally aware teaching strategies which can help foster a more inclusive and supportive physical education environment where Muslim women student will not compromise their faith.